Mathematical model of milk secretion in a cow’s udder - A. G. Senkov; I. I. Girutski; A. B. Grischenko (Системный анализ и прикладная информатика, 2019)
The paper proposed a mathematical model that describes the dynamics of the physiological process of milk secretion in the cow’s udder, depending on the value of the time interval that has passed since the end of the last milking. The intensity of this process, and, consequently, the cow’s milk production level, depends, among other things, on the optimal choice of the multiplicity of milkings per day with certain time intervals between milkings. The proposed model will allow to take into account these factors in the analysis and optimization of conditions for the maintenance of dairy cattle herds. The results of the research are applicable in diagnosing the state of a cow, in a comparative assessment of the effectiveness of milking multiplicity, etc. The model’s determination coefficient is 0.82 for the aperiodic link used as a model. The advantage of the proposed approach to the identification of a biological object – a cow – is the use of a passive experiment technique based on statistical processing of experimental data on yields recorded by modern information systems for the management of cattle on existing dairy farms.